Critical Exploration of Liquid Metal Plasma-Facing Components in a Fusion Nuclear Science Facility. (17th November 2019) - Kessel, C. E.; Andruczyk, D.; Blanchard, J. P.; Bohm, T.; Davis, A.; Hollis, K.; Humrickhouse, P. W.; Hvasta, M.; Jaworski, M.; Jun, J.; Katoh, Y.; Khodak, A.; et al.
Abstract: Liquid metal (LM) plasma-facing components (PFCs) may provide a resolution to the challenging fusion environment, particularly the first wall and divertor surfaces. Transforming these concepts into viable technologies will require considerable research and development. With the fusion nuclear regime in mind, the Fusion Energy System Studies group examined LM PFCs in order to identify needed research thrusts that could accelerate their development and assess their viability. Liquid metal behavior, solid substrate aspects, and fusion facility integration aspects are examined, with concepts as the research focusing element. The concepts applied to a fusion nuclear device are the primary definer of the LM parameters, environmental conditions, and operational aspects. This forms the research strategy recommended for these complex systems.